Shrinkage of thyrotrophin secreting pituitary adenoma treated with octreotide. Issue 787 (May 1991) - Orme, S. M.; Lamb, J. T.; Nelson, M.; Belchetz, P. E.
Abstract : Thyrotrophin secreting pituitary adenomas are a rare cause of recurrent thyrotoxicosis. We report on a 47 year old woman with an 8-year history of this condition. In this case the somatostatin analogue, octreotide, normalized thyroid hormone levels. It was associated with marked tumour shrinkage, with striking reduction of the suprasellar extension and improved appearances in the region of the left cavernous sinus shown by high resolution computerized tomography. Following surgery she developed a biochemical relapse which responded to the reinstitution of octreotide. On long term treatment she developed stomach cramps and gallstones. Octreotide was discontinued. We review previous reports of this condition and discuss the role of octreotide in its management.